Upaya Peningkatan Disiplin Kerja dalam Menunjang Produktivitas Kerja Karyawan di Levi’s Factory Outlet Store Teuku Umar - Ni Made Dwi Puspitawati; Komang Tri Wahyuni; I Gede Darma Putra (Jurnal Ilmiah Pengabdian dan Inovasi, 2022)
This community service activity is carried out with the aim that employees have high discipline, increase employee work productivity, increase employee confidence when serving and promoting products to potential customers. Several special activities were carried out in an effort to increase sales during the Covid-19 period, where these activities started from August 11 to September 17, 2022. Through this activity, it is hoped that employees will be able to improve work discipline in supporting work productivity so that this is expected to have an impact on increase in sales during the current Covid-19 pandemic. After an evaluation of the work program that has been implemented, an increase in the company's turnover has begun. Thus, continuous evaluation needs to be carried out for improvements that may be made by the company in order to achieve the company's goals.